Production of Carbon Nanotubes for Gas Sensor Application - Md. Yasin, Faizah (2006)
Gas sensors have a wide application in everyday life, whether in industry, medical, agriculture and environmental monitoring. A good sensor should be selective, sensitive, responsive, reliable and cost effective. Currently available gas sensors are lacking in one or more of these criteria. Therefore, there is a need to develop new sensing materials and technologies.